2006
DOI: 10.1038/sj.npp.1301129
|View full text |Cite
|
Sign up to set email alerts
|

Mecamylamine Attenuates Cue-Induced Reinstatement of Nicotine-Seeking Behavior in Rats

Abstract: Mecamylamine, a noncompetitive nicotinic cholinergic antagonist, inhibits nicotine self-administration in animals and may attenuate tobacco smoking in humans trying to quit. Our preliminary data suggested that this agent, at a dose of 2 mg/kg (subcutaneous (s.c.)), also attenuates cue-induced relapse to nicotine-seeking behavior in rats. This study determined whether mecamylamine-induced attenuation can be obtained at doses lower than the high 2 mg/kg dose used in the first study, and whether it is specific to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
2
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 88 publications
5
42
2
2
Order By: Relevance
“…It is especially promising that in this study clofibrate had a protective effect against both nicotine-and cue-induced reinstatement. Clofibrate's ability to counteract nicotinerelated cues is consistent with the findings that PPARa agonists downregulate nicotinic receptors and that cue-induced nicotine-seeking depends upon the action of acetylcholine at nicotinic receptors (Liu et al, 2007). If clofibrate can indeed counteract the effects of smoking-related cues, this could make it a valuable adjunct or alternative to bupropion, varenicline, and nicotine patch therapies, which do not appear to protect against cueinduced nicotine craving in humans (Ferguson and Shiffman, 2009) or cue-induced nicotine-seeking in rats (Wouda et al, 2011;Liu et al, 2008).…”
Section: Discussionsupporting
confidence: 73%
“…It is especially promising that in this study clofibrate had a protective effect against both nicotine-and cue-induced reinstatement. Clofibrate's ability to counteract nicotinerelated cues is consistent with the findings that PPARa agonists downregulate nicotinic receptors and that cue-induced nicotine-seeking depends upon the action of acetylcholine at nicotinic receptors (Liu et al, 2007). If clofibrate can indeed counteract the effects of smoking-related cues, this could make it a valuable adjunct or alternative to bupropion, varenicline, and nicotine patch therapies, which do not appear to protect against cueinduced nicotine craving in humans (Ferguson and Shiffman, 2009) or cue-induced nicotine-seeking in rats (Wouda et al, 2011;Liu et al, 2008).…”
Section: Discussionsupporting
confidence: 73%
“…Smoking denicotinized cigarettes (i.e., cue alone) produces an equal amount of smoke intake and similar or even higher levels of satisfaction compared to nicotine-containing cigarettes (i.e., cue plus nicotine) (Butschky et al 1995;Gross et al 1997;Rose et al 2000). In recent animal studies, we (Liu et al 2006;Liu et al 2007) and others (LeSage et al 2004;Cohen et al 2005;Paterson et al 2005) have found that reintroduction of nicotine-associated cues after extinction resulted in increased responding on the lever previously reinforced by nicotine delivery. Taken together, these data indicate that environmental stimuli repeatedly associated with the administration of nicotine acquire conditioned incentive value, which critically contributes to reinstatement of nicotine-seeking behavior in animals and smoking relapse in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these sensory cues seem to be particularly important in highly addicted smokers (Brauer et al 2001). Additionally, in experimental animals high rates of responding for nicotine are only observed in the drug infusions are paired with a sensory stimulus (Caggiula et al Following extinction of responding for nicotine, the presentation of a cue previously paired with the nicotine infusions elicits reinstatement of responding (LeSage et al 2004;Liu et al 2007). Cueinduced reinstatement of nicotine-seeking behaviour is attenuated by the prior administration of the mGluR5 antagonist MPEP (Bespalov et al 2005).…”
Section: Mglur5 Receptors and Models Of Relapsementioning
confidence: 99%
“…mGluR5 receptors regulate the activation of glutamate NMDA receptors acting as an enhancer of NMDA-activated currents and increased phosphorylation of the receptor through intracellular signalling MAPK/ERK and calcium responsive element binding (O'Brien et al 2004;Liu et al 2007) via a Src-family tyrosine kinase (Kotecha et al 2003).…”
Section: Neurobiology Of Mglur5mentioning
confidence: 99%